Perspectives of Patients, Caregivers and Researchers on Research Priorities in Donation and Transplantation in Canada: A Pilot Workshop. Issue 2 (February 2017) - Allard, Julie; Durand, Céline; Anthony, Samantha J.; Dumez, Vincent; Hartell, David; Hébert, Marie-Josée; West, Lori J.; Wright, Linda; Fortin, Marie-Chantal
Abstract : Background: It is vitally important to seek input from key stakeholders to increase the quality and relevance of health-related research and accelerate its adoption into practice. Patients and caregivers have rarely been involved in setting research priorities in the transplantation and donation field. The objectives of this explorative study are: (i) to discuss research priorities within the Canadian National Transplant Research Program during a priority-setting exercise with patients, caregivers, organ donors and researchers and (ii) to compare the identified priorities with research published in 2 prestigious transplantation journals. Methods: A pilot workshop attended by 10 patients and caregivers and 5 researchers was held in Montréal (Quebec, Canada) in August 2014 to identify research priorities. Priorities were identified using a thematic analysis of the workshop transcription conducted by multiple coders. These priorities were compared with the topics of research articles published in 2 major transplantation journals between 2012 and 2014. Results: The themes of the 10 research priorities identified by study participants were related to different research domains: social, cultural, and environmental health factors (4); biomedical or clinical (4); and research about health systems and services (2). 26.7% of the research articles published were related to the identified priorities. Thirteen percent looked at ways to improve graft survival and 8.5% looked at the development of tolerance, 2 priorities identified by participants. Fewer than 5% examined the other 8 research priorities identified as important by workshop participants. Conclusions: This is the first study reporting patients' and researchers' priorities in the field of transplantation and donation in Canada. There is a discrepancy between topics that key stakeholders find important and research published in 2 major transplantation journals. The research priorities identified during our initial workshop will be validated through a national survey and workshop.